“Building the plane while flying it” Reflections on pandemic preparedness and response; an organisational case study - Karen McKenna; Stéphane Bouchoucha; Bernice Redley; Anastasia Hutchinson (BMC Health Services Research, 2023)
Abstract Background The COVID-19 pandemic provided a unique opportunity to learn about acute health organisations experiences implementing a pandemic response plan in real-time. This study was conducted to explore organisational leader’s perspectives and experience activating a COVID-19 pandemic response plan in their health service and the impact of this on service provision, clinicians, and consumers. Methods This study was conducted at a large metropolitan health service in Australia that provides acute, subacute, and residential aged care services. Semi-structured interviews were conducted with 12 key participants from the COVID-19 leadership team between November-January 2021/2022. A semi-structured interview guide was developed to explore how the health service developed a clinical governance structure, policy and procedures and experience when operationalising each element within the Hierarchy of Controls Framework. Thematic analysis was used to code data and identify themes. A cross-sectional survey of frontline healthcare workers on the impacts and perceptions of infection control practices during the COVID-19 pandemic, was also completed in 2021 with 559 responses. Results Twelve organisational leaders completed the semi-structured interviews. Key themes that emerged were: (1) Building the plane while flying it, (2) A unified communications strategy, (3) Clinicians fear ‘my job is going to kill me’, (4) Personal Protective Equipment (PPE) supply and demand, and (5) Maintaining a workforce. When surveyed, front-line healthcare workers responded positively overall about the health services pandemic response, in terms of communication, access to PPE, education, training, and availability of resources to provide a safe environment. Conclusion Health service organisations were required to respond rapidly to meet service needs, including implementing a pandemic plan, developing a command structure and strategies to communicate and address the workforce needs. This study provides important insights for consideration when health service leaders are responding to future pandemics. Future pandemic plans should include detailed guidance for acute and long-term care providers in relation to organisational responsibilities, supply chain logistics and workforce preparation.